2017
DOI: 10.1159/000471481
|View full text |Cite
|
Sign up to set email alerts
|

Benign Exocrine Pancreatic Diseases in Inflammatory Bowel Diseases

Abstract: Background: Data regarding the involvement of the pancreas during the course of inflammatory bowel disease (IBD) are scarce and conflicting. Aim: To assess the frequency of benign pancreatic diseases, that is, acute pancreatitis, chronic pancreatitis (CP), and autoimmune pancreatitis (AIP), in a population with IBD. Methods: A search for patients with IBD who presented at our hospital between January 2006 and January 2015 with a diagnosis of IBD was carried out. Patients: A total of 5,242 patients with IBD wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…[10][11][12] However, its prevalence varies among reported studies (0.04-4.5%). [13][14][15][16][17] Although data regarding the global prevalence of AIP are still lacking, 18 Japanese nationwide epidemiological survey of AIP demonstrated that the prevalence of AIP among general population was 10.1 per 100,000 persons, 18 suggesting a higher prevalence of AIP in patients with IBD.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] However, its prevalence varies among reported studies (0.04-4.5%). [13][14][15][16][17] Although data regarding the global prevalence of AIP are still lacking, 18 Japanese nationwide epidemiological survey of AIP demonstrated that the prevalence of AIP among general population was 10.1 per 100,000 persons, 18 suggesting a higher prevalence of AIP in patients with IBD.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] However, a case series revealed no significant rise in the occurrence of pancreatitis among individuals with IBD when compared to the general population . [ 13 ] Hence, the existence of a causal relationship between IBD and acute pancreatitis remains uncertain.…”
Section: Introductionmentioning
confidence: 99%